104 Sodium valproate subcutaneous infusion; a valuable adjunct in the management of neuropathic pain in palliative patients. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Davis, C; Crispin, HK; Marshallsay, C; Haig, S; Pennell, S; Jenks, A
Abstract : Introduction: Sodium valproate continuous subcutaneous infusion (CSCI) may be underutilised in the multi-modal management of neuropathic pain especially for patients requiring parenteral pain management due to phase of illness or symptom severity. We present a case series of adult patients treated with a sodium valproate CSCI. Method: Prospective data collection; six consecutive clinical cases managed by the Hospital Specialist Palliative Care Team (HSPCT) during final quarter of 2017. Sodium valproate was commenced at a dose of 200–600 mg/24 hour, in conjunction with a separate opioid or midazolam CSCI. Doses were up-titrated individually to between 400 mg/24 hour and 1500 mg/24 hour (maximal increments of 300 mg/24 hour). Results: 4/6 patients had metastatic cancer, one cervical myelopathy and one osteoradionecrosis of the base of his skull; all had clinical reasons to require parenteral treatment. 5 experienced clinically significant improved pain control within 48 hours; allodynia resolved in the two patients who experienced this, one of whom had residual severe nociceptive pain due to rapidly progressive disease. There was no initial benefit attained in the patient whose starting dose was 200 mg/24 hour, but a dose of 400 mg/24 hour was beneficial. There were no complications attributable to this treatment. Only 2/6 patients required an increase in opioid dose. Conclusion: Unlike most neuropathic pain agents, sodium valproate is available in a parenteral preparation. Other benefits include that it is non-sedating and relatively safe in patients with renal impairment although dose modification is recommended. Six patients with a neuropathic component to their pain treated with sodium valproate CSCI as part of a multi-modal analgesic strategy achieved rapid, efficacious control of their neuropathic pain. Titration was achieved over the course of days, the treatment was well-tolerated. We have found a starting dose of 400 mg/24 hour to offer clinically relevant improvement in pain control. This case series supports our impression that it is an opioid sparing intervention.